O contexto e a compreensão lexical na leitura em português: língua estrangeira - Regina Lucia Peret Dell Isola (1999)
This research investigates the effect of context on the comprehension of lexical items during the process of reading in Portuguese as a foreign language (PFL), given that reading has been seen as an efficient task for the learner to acquire new words, or new meanings for words they already know, and therefore increase their vocabulary in the target language. Although the literature highlights the importance of context on lexical comprehension, there are no conclusive data regarding this question. The evidence of a possible positive effect on the elucidation of the meaning of unknown (or unrecognised) lexical items by learners of PFL is investigated here, where the notion of comprehension is restricted to the stage at which the reader seeks to construct a meaning for an item, demonstrating comprehension by paraphrase, that is, by attributing an adequate meaning to the text being read. The problem is investigated from two different and complementary points of view; quantitative and qualitative analyses of the data collected from 93 participating subjects were made. The test was the principal statistic measure used to evaluate the results quantitatively. As a basis for the study of dispersion frequencies the following were verified: 1) the relativity of the positive effect of context on comprehension in the subjects; 2) the existence of different degrees of difficulty in the lexical items for the group of learners who participated in this research; 3) the presence of different degrees of efficiency for context on the comprehension of these items. The qualitative data were combined with reports from the subjects in retrospective interviews. Thus, given the complexity of the phenomenon of reading which involves the interaction of various components, an interactive model was elaborated as the most convenient for describing the mechanisms of reading in PFL in order to verify to what extent verbal context (the lexical item itself, the sentence structure in which the item is contained, the totality of the discourse) and the non-verbal context (previous knowledge, memory, affect, amongst others) could contribute to lexical comprehension. In this sense, we sought to describe those resources used by learners of PFL in searching for a meaning for unknown or unrecognised lexical items, during the reading of an authentic text (written in Portuguese by a Brazilian author, with no didactic aim in mind).